A randomised, double-blind clinical phase II trial of the efficacy, safety, tolerability and pharmacokinetics of a single dose combination treatment with artefenomel and piperaquine in adults and children with uncomplicated Plasmodium falciparum malaria - Macintyre, Fiona; Adoke, Yeka; Kibuuka, Afizi; Tshefu, Antoinette Kitoto; Phuc, Bui Quang; Ouedraogo, Alphonse; Ramharter, Michael (BMC medicine, 2017)
The clinical development of a single encounter treatment for uncomplicated malaria has the potential to significantly improve the effectiveness of antimalarials. Exploratory data suggested that the combination of artefenomel and piperaquine phosphate (PQP) has the potential to achieve satisfactory cure rates as a single dose therapy. The primary objective of the study was to determine whether a single dose of artefenomel (800 mg) plus PQP in ascending doses is an efficacious treatment for uncomplicated Plasmodium falciparum malaria in the 'target' population of children ≤ 5 years of age in Africa as well as Asian patients of all ages.